The Brand Image and Its Effect on Consumer Loyalty and Satisfaction as a Variable Intervening of Aqua Mineral Water Product (Study on Undergraduate Student of Management Study Program, Universitas Simalungun) - Pandapotan Simatupang; Fariaman Purba (Budapest International Research and Critics University, 2020)
Brand Image and its influence on consumer loyalty and consumer satisfaction as intervening variables of Aqua Mineral Water Products (study on undergraduate student of Management Study Program, Universitas Simalungun). The purpose of this research is to find out how the influence of brand image on consumer loyalty by interviening variable consumer satisfaction. The formulation of the problems of this study, 1). Does brand image influence consumer satisfaction of Aqua Mineral Water product?, 2). Does consumer satisfaction affect consumer loyalty Aqua Mineral Water product?, 3). Does brand image influence consumer loyalty of Aqua Mineral Water product?, 4). Does brand image influence customer loyalty through customer satisfaction as an intervening variable for Aqua Mineral Water product? The sampling technique used purposive sampling with the consideration that the respondents were students who had consumed Aqua brand mineral water for 77 respondents. The analysis technique used is a simple linear analysis technique and by using path analysis, then it is processed using SPSS Version 24. From the research result obtained by regression equation 1). Z = 10.861 + 0.457 (X) + 0.77, and from equation 2). Y = 11,943 + 0,230 (X) + 0,233 (Z) + 0,93. The results of this study indicate that the brand image variable (X) has a positive and significant effect on poverty (Z) shown by a positive coefficient of 0.457 and a significance of 0.000<0.05. Satisfaction (Z) has a positive and not significant effect on loyalty (Y) with a positive coefficient of 0.233 and a significance of 0.257>0.05. Brand image (X) has a positive and significant effect on loyalty (Y) with a positive coefficient of 0.230 and a significance of 0.038<0.05. Satisfaction is able to provide an intervening effect and significant positive influence on 2 variables of brand image and loyalty with a positive coefficient of 0.230 (X); 0.233 (Z) and significance 0.181<1.66.